(3R,4S,5R,6R,7S)-3,4,5,7-Tetrahydroxyconidine, an azetidine analogue of 6,7-diepicastanospermine and a conformationally constrained d-deoxyaltronojirimycin, from l-arabinose. - Martínez, R; Araújo, N; Jenkinson, S; Nakagawa, S; Kato, A; Fleet, G (2013)
The synthesis from l-arabinose of an azetidine analogue of 6,7-diepicastanospermine and its glycosidase inhibition profile are described.